Lean Project Management - How to Apply Lean Thinking to Project Management - Erne, Rainer (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
This book shows how the principles of Lean Management can be applied to project management and how some typical problems of the latter can be solved by this. This book is a translation of the original German 1st edition Lean Project Management - Wie man den Lean-Gedanken im Projektmanagement einsetzen kann by Rainer Erne, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2019. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content. The author first provides a more theoretical description of what project management is about and what the key ideas of 'Lean' consist of. Based on these foundations, five principles of 'Lean Project Management' are derived. Along these principles, the author then elaborates typical current challenges of project management and shows how these challenges can be tackled through Lean Project Management. In doing so, he does not stop at the level of principles, but describes specific tasks and tools that are useful especially for experienced practitioners of project management. The Content What is the meaning and use of project management? What are the key ideas of 'Lean'? How can projects be managed in a 'Lean' way? Can "Lean Project Management" be standardized throughout the organization? The Author Rainer Erne is Professor of Product, Process and Project Management at Nuertingen-Geislingen University. He previously worked for over 15 years as a project manager in various companies and is a certified Project Management Professional (PMP).
What is and what is the use of project management? -- What does the lean idea consist of? -- How can projects be managed leanly? -- Can lean project management be standardized throughout an organization?.
Keywords: Management; Project management; Management; Project Management